2013
DOI: 10.1080/14330237.2013.10820637
|View full text |Cite
|
Sign up to set email alerts
|

Student Nurses' Experiences of The Clinical Psychiatric Learning Environment in an Education Institution

Abstract: This study investigated lived experiences of student nurses working in a clinical psychiatric learning environment in South Africa. Participants were 29 fourth-year student nurses in the clinical psychiatric learning environment at a nursing education institution (females = 27; males =2). They engaged in focus group discussion on their experiences of the clinical psychiatric learning environment. The data were thematically analyzed using Tesch's method of open coding. The student nurses experienced the environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
4
5
0
1
Order By: Relevance
“…This finding is supported by Moagi, Van Rensburg and Maritz ( 2013 :54) in their study conducted in Pretoria, South Africa, which revealed that male nursing students experience isolation which may be derived from being male in a predominantly female career. Another participant re-affirmed the female dominance when he reported ‘… we can’t deny that this profession is dominated by women …’ (FG1, P3).…”
Section: Ethical Considerationssupporting
confidence: 52%
“…This finding is supported by Moagi, Van Rensburg and Maritz ( 2013 :54) in their study conducted in Pretoria, South Africa, which revealed that male nursing students experience isolation which may be derived from being male in a predominantly female career. Another participant re-affirmed the female dominance when he reported ‘… we can’t deny that this profession is dominated by women …’ (FG1, P3).…”
Section: Ethical Considerationssupporting
confidence: 52%
“…; Moagi et al. ) and with a new curriculum (Daniels & Khanyile ) and their academic integrity (Theart & Smit ) have been studied in South Africa; however, no studies were found of nursing education practices in Uganda.…”
Section: Discussionmentioning
confidence: 99%
“…The third model, which was found primarily in texts looking at the medical sciences, is focused on how personal transformation comes from unusual situations or special educational practices, as are found in service learning and collaborative projects. In a number of studies these are positioned as only coming from outside the traditional curriculum and experiences of students (Berman & Allan, 2012;Efthimiadis-Keith, 2007; Janse van Rensburg, Poggenpoel, & Myburgh, 2012;Moagi, van Rensburg, & Maritz, 2013;Stears, 2009;Sutherland, 2013). As the innovations explored in these texts are largely situated outside of the academic curriculum, they tend to focus on how students' experiences help them to develop a new understanding of South African society, rather than how this is informed by their engagement with academic knowledge.…”
Section: The Overall Models Of Students' Personal Transformationmentioning
confidence: 99%